Research on non-uniform pressure pulsation of the diffuser in a nuclear reactor coolant pump - Qiang Zhou; Hongkun Li; Lin Pei; Zuowen Zhong (Nuclear Engineering and Technology, 2021)
The nuclear reactor coolant pump transferring heat energy inherently brings with it the unsteady flow and inevitably threatens to the safe operation of the pump unit, especially with the pressure pulsation induced by the rotor-stator interaction. In this paper, the characteristics of pressure pulsation of the diffuser in a nuclear reactor coolant pump were investigated by the numerical simulation with experimental validation. Pressure pulsation signals measured synchronously from sensors mounted on the radial diffuser of a model pump were analyzed via Welch’s method. Frequency components induced by the rotor-stator interaction can be revealed by the diameter mode analysis method. The pressure pulsation of the diffuser is dominated by the blade passing frequency and its harmonics, which are free from the effect of flow rate and rotational speed while the corresponding amplitudes are easily affected by different operational conditions and measuring positions. The non-uniformity is much more affected by the rotational speed than the flow rate. This research is helpful for further work to reduce the pressure pulsation for the reactor coolant pump.